Peran Teknologi Digital dalam Meningkatkan Pendidikan Akuntansi: Tinjauan Sistematik - putri, Fadya shakira; Novianti Novianti; Gunawan Aji (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the role of digital technology in enhancing accounting education using a systematic literature review approach. A total of ten relevant articles published over the past ten years were selected based on specific inclusion criteria and analyzed using the PICO framework (Population, Intervention, Comparison, Outcome). The findings indicate that the integration of digital tools such as e-learning platforms, simulation software, and digital games has positively contributed to improving students’ academic performance, motivation, practical competencies, and career readiness in the accounting field. Unlike previous studies that tended to focus on isolated cases or short-term impacts, this research provides a comprehensive synthesis across multiple contexts and highlights the interplay between technological readiness, curriculum design, and institutional support. The study concludes that successful digital transformation in accounting education requires collaborative efforts between lecturers, students, and institutions, alongside sustained infrastructure development and professional training. Future research is recommended to include empirical validation and cross-cultural perspectives to deepen insights into the long-term effectiveness of digital technology integration in higher education accounting programs.